IMPLEMENTASI KEBIJAKAN PEMBELAJARAN BAHASA JAWA SEBAGAI MUATAN LOKAL KELAS IV DI MI PLUS AL-KAUTSAR YOGYAKARTA - Nurul Ana Sulaikha; Sedya Santosa (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The destination of this research is to knowing about fungtion of Javanese language studying from two sides: 1) purpose and fungsion from Javanese language studying as a local subject for class IV at Al-kautsar elementary school Yogyakarta, 2) realization of Javanese language studying as a local subject for class IV at Alkautsar elementary school Yogyakarta. The type of this research is qualitative research with descriptive analysis method. The technique of collecting data are interview, observation, and documents collection. Codification, presentation, and withdrawal of conclusions or verifications. This research used a triangulation technique for checking the validity of the findings. There are two conclusion from this research: 1) the direction or purpose and function of learning Javanese language class IV in MI Plus Al-kautsar doesn’t going well as a DIY governor regulation number 64 of 2013. 2) the implementation of class IV Javanese language learning in MI Plus Al-kautsar for its curriculum has followed the 2013 curriculum. In Javanese language leraning, the meeting time is only two hours in a week, and it’s was utilized as much as possible by Mrs. Muthi as a Javanese language teacher. In the learning process, she not only conveys the material, but she also provides motivation to students, inviting them to talk about their experiences in accordance with the theme under discussion, and by this method the students being active in the study. Delivery of motivation is done at the beginning of learning and at the end of learning, while for the evaluation or assessment of learning she only uses written assessment technique.